Association of Bone Metabolism Indices and Bone Mineral Density with Diabetic Retinopathy in Elderly Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Inpatient Study in China - Xin Zhao; Lili Huo; Xiaofeng Yu; Xiaomei Zhang (Journal of Diabetes Research)
Objective. This study is aimed at analyzing the association between bone metabolism indices and diabetic retinopathy (DR) in elderly patients with type 2 diabetes mellitus. Methods. Data of 352 men and 284 postmenopausal women, aged more than 50 years, with type 2 diabetes mellitus were retrospectively analyzed. Patients were divided into three groups based on the degree of DR: nondiabetic retinopathy (NDR) group, background diabetic retinopathy (BDR) group, and proliferative diabetic retinopathy (PDR) group. Results. (1) The diabetic duration and urinary albumin to creatinine ratio (UACR) were significantly higher in the PDR and BDR groups than in the NDR group (P<0.05). The level of beta-C-terminal telopeptide (β-CTX) in male patients was lower in the PDR and BDR groups than in the NDR group (P<0.05). In addition, the level of procollagen 1 intact N-terminal (P1NP) in female patients was higher in the PDR and BDR groups than in the NDR group (P<0.05). (2) For men and postmenopausal women, the proportion of vitamin deficiency was higher in the PDR and BDR groups than in the NDR group (P<0.05). (3) The logistic regression analysis in men and postmenopausal women showed that the diabetic duration and lower levels of UACR and 25(OH)D were independent risk factors for DR (P<0.05). (4) The diabetic duration was also an independent risk factor for PDR (P<0.05); however, no independent correlation was found between the level of 25(OH)D and PDR (P>0.05). Conclusions. A close association was observed between 25(OH)D level and DR in the elderly male patients and postmenopausal women with type 2 diabetes mellitus. P1NP and β-CTX levels might be closely related to DR in elderly male patients and postmenopausal women with type 2 diabetes mellitus.